Peranan Motivasi dan Pengembangan Karier dalam Meningkatkan Kinerja Guru SMK Mudita Kota Singkawang - Harina Tjong (Educatio, 2025)
This research is motivated by the important role of motivation and career development in improving teacher performance, particularly at SMK Mudita in Singkawang City, a vocational school focused on improving the quality of vocational education. The purpose of this study was to analyze the influence of motivation and career development on teacher performance, both partially and simultaneously. The research method used was a quantitative survey approach. Data collected through questionnaires were analyzed using validity and reliability tests, as well as multiple regression analysis. Based on the validity test, the variables of motivation, career development, and performance were all declared valid, with a Pearson Correlation value > 0.422. The Cronbach's Alpha test result was 0.943, indicating very high instrument reliability. Meanwhile, for descriptive data, the average scores for motivation (86.09), career development (83.20), and teacher performance (82.47) were in the high category, indicating that good motivation and career development contribute positively to improved performance. The results of the study indicate that motivation has a positive and significant influence on teacher performance, as does career development, which also contributes significantly to performance improvement. Simultaneously, motivation and career development together explain 77.8% of the variation in teacher performance, with career development as the dominant factor. The conclusion of this study confirms that integrated management of motivation and career development is crucial for achieving optimal teacher performance in vocational schools, particularly at SMK Mudita in Singkawang. Therefore, it is recommended that schools and stakeholders focus on improving teacher motivation and career development as the main strategy in managing human resources in vocational education.